STUDENTS’ PERCEPTION ON THE USE OF CONTENT-BASED INSTRUCTION IN LEARNING ENGLISH FOR NURSING - Fitriani, Artika Wina; Purwandari, Gigih Ariastuti; Puspitasari, Indah (Media Inovasi Pendidikan dan Publikasi, 2025)
Teaching English to learners should have specific goals and purposes. English for nursing is considered teaching English for specific purposes. Mastery of English is a very important aspect for nurses who are involved in medical services. The lesson of English for nursing requires the teacher to choose an appropriate teaching method. This study focused on Students’ perception on the use of content-based instruction in learning English for nursing. It examines the learner’s views towards the use of content-based instruction in teaching English for nursing, how well content-based instruction supports learners to master English for nursing, the challenges The subject of the research were 41 nursing students of Politeknik Yakpermas Banyumas. It used a descriptive quantitative approach. The data were gathered through interviews and questionnaires. The results of this study showed that the learners have a positive view towards using content-based instruction in teaching English for nursing. The positive learner’s view is the topics, materials, and activities used in class are relevant, meaningful, interesting, and useful to them in learning English for nursing. Content-based instruction supports learners to master English for nursing: learners actively participate in the learning process, learners use language for communicative purposes rather than grammatical patterns and learners develop their English language skills. Moreover, this study hopefully will contribute to the field of EFL teaching methodology as the study of English for specific purposes and in education research.